2011
DOI: 10.14436/2178-3713.1.1.058-063.oar
|View full text |Cite
|
Sign up to set email alerts
|

Root canal filling with calcium hydroxide paste using lentullo spiral at different speeds

Abstract: Objective: This study analyzed the effectiveness of filling the root canal with calcium hydroxide paste using the Lentulo spiral at different speeds. Methods: Thirty mandibular premolars after root canal preparation were divided in three groups. Calcium hydroxide paste was inserted in the root canals with a Lentulo spiral at 5,000 rpm (G1), 10,000 rpm (G2) and 15,000 rpm (G3). The optical density was determined by the use of the digital radiography system Kodak Dental RGV-5000. Results: The highest optical den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…Torres et al 20 suggested to select a lentulo spiral that is easily placed to the working length without binding the canal walls. Estrela et al 5 and Deonizio et al 21 , in their studies, used lentulo spiral at 3 mm short from the working length. Torres et al 20 and Simcock and Hicks 22 used lentulo spiral at working length.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Torres et al 20 suggested to select a lentulo spiral that is easily placed to the working length without binding the canal walls. Estrela et al 5 and Deonizio et al 21 , in their studies, used lentulo spiral at 3 mm short from the working length. Torres et al 20 and Simcock and Hicks 22 used lentulo spiral at working length.…”
Section: Discussionmentioning
confidence: 99%
“…Deveaux et al 23 preferred the speed of 500 rpm; whereas, Rahde et al 24 and Caliskan et al 25 only entitled as low and moderate speeds, without particularizing it. Deonizio et al 21 used 5000 rpm, 10000 rpm and 15000 rpm in their experimental groups which are quite realistic speeds for clinical use. Therefore, in the present study, lentulo spiral was used at different speeds as 20000 rpm, 10000 rpm and 5000 rpm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Calcium hydroxide should be applied in sufficient amounts into the root canal in order to be able to provide adequate concentration of calcium and hydroxyl ions to exert their biological effects. 6 Calcium hydroxide kills the microorganisms by direct contact. Thus, in order to achieve maximum biological effects, calcium hydroxide should be applied and spread uniformly and with the highest density along the canal working length.…”
Section: Introductionmentioning
confidence: 99%
“…[12,13] Also Deonízio et al reported that the 15,000 rpm speed was more effective in filling the apical third and 5,000 rpm speed was more effective in filling the cervical and middle thirds in their study utilizing lentulospirals at different speeds for filling the root canal with calcium hydroxide paste. [14] However, Bawazir and Salama evaluated in vivo two different obturation techniques, lentulospiral mounted in a slow speed handpiece and hand-held in primary teeth. Authors concluded that there was no statistically significant difference between the two techniques of obturation, according to the quality of the root canal filling or success rate.…”
Section: Introductionmentioning
confidence: 99%